2015
DOI: 10.2134/jeq2014.04.0195
|View full text |Cite
|
Sign up to set email alerts
|

Metal Leaching in Mine Tailings: Short-Term Impact of Biochar and Wood Ash Amendments

Abstract: Biochar is perceived as a promising amendment to reclaim degraded, metal-contaminated lands. The objective of this study was to compare the potential of biochar and wood ash amendments to reduce metal(loid) leaching in mine tailings. A 2-mo leaching experiment was conducted in duplicate on acidic and alkaline tailings, each mixed with 5 wt.% of one of the following amendments: three wood-derived, fast-pyrolysis biochars (OC > 57 wt.%) and two wood ash materials (organic carbon [OC] ≤ 16 wt.%); a control test w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 35 publications
0
13
0
Order By: Relevance
“…Total IC refers to total inorganic C. Data points correspond to the following: 1 = Airex 1; 2 = Airex 2; 3 = Pyrovac; 4 = BassWd 400; 5 = BassWd 450; 6 = Willow 450; 7 = Willow 500; 8 = BasquesC; 9 = BasquesF; 10 = SGrass 400; 11 = SGrass 500; 12 = Poultry litter 450; 13 = Poultry litter 500; 14 = WdAsh A; 15 = WdAsh B. For samples digested using two different methods, A are samples acid-digested using aqua regia without hydrofluoric acid (HF) and B are samples acid-digested with HF, as published by Beauchemin et al 7 Loadings plots are shown in the Supporting Information (Figure S1).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Total IC refers to total inorganic C. Data points correspond to the following: 1 = Airex 1; 2 = Airex 2; 3 = Pyrovac; 4 = BassWd 400; 5 = BassWd 450; 6 = Willow 450; 7 = Willow 500; 8 = BasquesC; 9 = BasquesF; 10 = SGrass 400; 11 = SGrass 500; 12 = Poultry litter 450; 13 = Poultry litter 500; 14 = WdAsh A; 15 = WdAsh B. For samples digested using two different methods, A are samples acid-digested using aqua regia without hydrofluoric acid (HF) and B are samples acid-digested with HF, as published by Beauchemin et al 7 Loadings plots are shown in the Supporting Information (Figure S1).…”
Section: Resultsmentioning
confidence: 99%
“…Organic C functional groups in Airex 2, BasquesF, Poultry litter 450, Pyrovac, SGrass 450, and Willow 450 were previously characterized. 11 Airex 1, BassWd 400, BassWd 450, WdAsh A, and WdAsh B were used in a study by Beauchemin et al on the impact of biochar on metal leaching from mine tailings; 7 Airex 2, BasquesF, Poultry litter 450, Pyrovac, SGrass 450, and Willow 450 were used in a study by Clemente et al on metal removal from solution. 11 The feedstock for Willow, SGrass, Poultry, Airex 2, and Pyrovac were chemically characterized to evaluate differences in element composition between feedstock and the resulting biochars.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The earlier studies did not focus on the quantity of biochar applied but more on the effects of various biochars on a wide range of soils and establishing the mechanisms of interaction [ 133 , 177 , 183 , 184 ]. Subsequently, researchers investigated the effects of biochar on Zn bioavailability in combination with plant species grown in contaminated soils.…”
Section: Effect Of Biochar On Specific Potentially Toxic Elements Mobility and Bioavailabilitymentioning
confidence: 99%
“…Of considerable interest is the profile for iron, which shows significant concentrations of iron in the pre-oxidized tailings, but with very low concentrations in the pore water of the unoxidized tailings. Previous studies analyzing acid digestion of the tailings from Q and P areas show that the pre-oxdized tailings are typically ~20-25% iron by weight (Beauchemin, Clemente, et al, 2014), Arsenic concentrations are shown to be high in initial saturation extraction from the unoxidized tailings, however, arsenic concentrations within all other measured tailings are significantly lower.…”
Section: Metal Cation Concentration Profilesmentioning
confidence: 86%